THE FINANCIAL RESOURCES OF INSURANCE COMPANIES AND DIRECTIONS OF THEIR PLACEMENT - D. Nesterova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article outlines the economic meaning of the financial resources of the insurance company. The structure of the financial resources of insurer financing is examined. The investment opportunities of financial resources are characterized. The role and place of the insurance company in the investment process are determined.